Nickel-Catalyzed Carbonylative Synthesis of Functionalized Alkyl Iodides - Peng, Jin-Bao; Wu, Fu-Peng; Xu, Cong; Qi, Xinxin; Ying, Jun; Wu, Xiao-Feng (iScience, 2018)
Functionalized alkyl iodides are important compounds in organic chemistry and biology. In this communication, we developed an interesting nickel-catalyzed carbonylative synthesis of functionalized alkyl iodides from aryl iodides and ethers. With Mo(CO) as the solid CO source, both cyclic and acyclic ethers were activated, which is also a challenging topic in organic synthesis. Functionalized alkyl iodides were prepared in moderate to excellent yields with outstanding functional group tolerance. Besides the high value of the obtained products, all the atoms from the starting materials were incorporated in the final products and the reaction had high atom efficiency as well.